Resveratrol alleviates MSU-induced gouty arthritis in rats through inhibition of HIF-1α- and NLRP3-derived IL-1β secretion in macrophages: Effect of Resveratrol on Gouty Arthritic Rats - Wang, Yamen; Li, Wei; Zhang, Tianhan; Wang, Runmei; Wang, Tao; Xie, Qingyun; Wei, Meng (Cellular and Molecular Biology, 2023)
Gouty arthritis is an acute and chronic joint inflammatory joint disease characterized by the deposition of monosodium urate (MSU) crystals in joints and periarticular tissues. Resveratrol (3, 5, 4-trihydroxy-trans-stilbene, RV), a natural polyphenolic compound, has anti-inflammatory and antioxidant properties. The purpose of this study was to investigate the effect of resveratrol on rats with gouty arthritis and its molecular mechanism. THP-1-derived macrophages were induced by lipopolysaccharide (LPS) and MSU to create an in vitro gout cell inflammation model, and rats were injected with MSU crystals into the right ankle joint for an in vivo acute gouty arthritis model. We investigated the anti-inflammatory properties of resveratrol using these in vitro and in vitro models. Our findings suggested that resveratrol effectively reduced ankle swelling and synovial inflammation in a dose-dependent manner in rats with acute gouty arthritis, with almost the same effect as colchicine treatment. In MSU-treated THP-1-derived macrophages, resveratrol inhibited NLRP3 inflammasome activation and IL-1β secretion. Furthermore, resveratrol and the HIF-1α inhibitor PX478 both inhibited the expression of the NLRP3 inflammasome, IL-1β, and HIF-1α. This study demonstrated that resveratrol significantly improved the symptoms of acute gouty arthritis and its potential mechanism may be IL-1β reduction via HIF-1α modulation and inhibition of NLRP3 inflammasome activation. Our study might offer a novel sight for the treatment of gouty arthritis.